Real-Time and Proactive SLA Renegotiation for a Cloud-Based System - Paputungan, I.V. (Institute of Electrical and Electronics Engineers Inc., 2018)
Cloud-based systems involve the management and control on the level of delivered service, which is crucial in order to maintain service continuity and customers’ trust for the service provided. Predefined service level agreement (SLA) is normally used as the main element in managing the cloud-based system. However, such SLA basically cannot be adjusted during operations. Current studies on SLA adjustment are mainly focused on modifying the agreement before commencing operations. The cloud environment is, however, dynamic and requires occasional review of the SLA parameters to manage expectations. Thus, to maintain service continuity that is acceptable to all parties, SLA adjustment is necessary during service operations. This paper presents a real-time and proactive SLA renegotiation model to support the dynamic nature of cloud-based systems. Renegotiation is shown for four different scenarios based on parameter weightage. In order to achieve real-time decision, a multi-offer generation approach is used. A novel mechanism to detect and predict service violation is proposed to ensure proactive renegotiation. Simulation is performed to verify the model. In the simulation, the model is found to be effective as it is able to generate multi-offers in a single renegotiation round and reduce the impact of service violations during service operations. IEEE